PENGARUH HARGA PRODUK DAN KURS TERHADAP VOLUME EKSPOR PRODUK MAN POLO SHIRT DI PT APPAREL ONE INDONESIA - Artdiana Evelyn PaskaSugeti; Sandi Supaya; Agus Suratno (Politeknik Negeri Semarang, 2017)
The aim of this study is to explain the influence of product prices and the exchange rate to the exports volume of Man Polo Shirt product both simultaneously and partially. The study utilized the secondary data from PT. Apparel One Indonesia and from Bank Indonesia. The analysis uses the multiple of linier regression statistic. According to data analysis report, it shows that product prices of Man Polo influence negative significantly to the Man Polo Shirt product’s export volume. Nevertheless, the exchange rate influence positif significantly to the Man Polo Shirt product’s export volume. The other result it shows that the product prices of Man Polo Shirt and the exchange rate simultaneously influence to the export volume of Man Polo Shirt product significantly. Suggestion to increase the exports volume of Man Polo Shirt product, PT. Apparel One Indonesia needs to pay more attention to product prices that they offer for importers because the export price is the most dominant influential variable in this study